Figurative derivational structure of mono- and polysemantic derivates as the subject of lexicography - Гуцуляк, Т.Є. (Studia Philologica, 2019)
In the system of figurative means of the Ukrainian language, the derivative lexical units, which were formed on the basis of figurative motivational relations, occupy a significant place. An important role in the recording and preservation of such figurative derivatives in the lexical-semantic system of the Ukrainian language is given to lexicographic works of an interpretive type. Dictionary definitions are important for establishing formal-semantic links of derivative units with their motivational basis and for defining motivational features. However, lexicographic interpretations are not always informative enough, but sometimes too generalized, which complicates the interpretation of figurative content of lexical units. Therefore, the purpose of the proposed work provides an analysis of the problematic issues of the present lexicographic practice of describing the semantic structure of morphological derivatives with a figurativelymetaphorical internal form and outlining the ways of their solution. The subject of the study is the following mono- and polysemantic units of the Ukrainian language, which, according to their structural and semantic features, belong to the derivatives from the subjective adjectives and contain sememes with figurative meaning. In the article on the example of separate adjectives the attention is focused on the need to take into account the vocabulary definitions of the peculiarities of the motivational traits that influenced the morphological structure and the semantic structure of the derivative word. This will help to provide a holistic understanding of the sign, called figurative derivative, given the possibility of implementing various aspects of the motivational semantics. Among the problematic issues of lexicographic practice, the formulation of vocabulary definitions for derivatives from the subjective adjectives is considered and the need to consider the ability of the nounmotivator to form not only relative (or possessively relative) adjectives, but also qualitative ones. It is suggested that the value of qualitative sign be fixed as independent lexico-semantic variants (LSV), since they often arise as a result of word-forming processes and testify to other semantic ties with the creators’ base.